A Study on the Utilization of Anthracitic Acid as a Reagent for Solvent Extraction of Tellurium Ion (IV) - A. H. AL- Haideri, A. M; Itawi, R. K; Hussain, A. F (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A study on solvent extraction of Tellurium with Anthranilic acid in water has been made. The effect of different parameters such as type of medium, time of equilibration, concentration of metal ion, solvent polarity and effect of anions and catins distribution ratio of tellrim (IV) were evaluated. The stoichometric ratio of the extracted species is determined by using two methods suh as slope analysis and mole ratio method and found to be (M: L) (1:4). The instability constant of complex was calculated as well.